INTEGRATED E-SUPPLY CHAIN MANAGEMENT SYSTEMS SERVICES AS A FORM OF ACCELERATION OF DEVELOPMENT IN INDONESIA - Pudjiastuti, Lilik; Indrawati, Indrawati; Ariski, Hasbi; Arianing Arrum, Desi; Pudjiastuti, Lilik (International Journal of Supply Chain Management, 2020)
Abstract? This article examines the effect of E-Supply Chain Management Systems in the Indonesia electronics services industry. It aims to review the ease of business licensing policy through the online system in the environmental field as a follow-up to the Online Single Submission Service policy which is intended to facilitate for entrepreneurs to obtain the legality of their business activities. Licensing in the environmental field aims to prevent environmental pollution and fulfill people's rights to obtain a good and healthy environment so that the existence of environmental licensing to achieve one of the Sustainable Development Goals (SDGs) targets, which is to reduce poverty and ensure equity development and environmental sustainability, especially the targets to minimize the danger of climate change caused by humans. Licensing service through OSS application is a policy that accelerates licensing services that have been considered long and expensive, but in the implementation of licensing services on line still raises legal problems, namely not fulfilling the principle of legal certainty, the principle of accuracy and the principle of transparency, so that the potential for business activities which has a license does not guarantee the creation of a good and healthy environment and achieving sustainable development. Discussion of this article through a conceptual analysis of licensing services and instruments for preventing pollution of the environment and analysis of laws and regulations in the field of environmental service sector licensing.